How to do the following:
\(if\quad x\quad =\quad cy\quad +\quad bz\\ \quad \quad \quad y\quad =\quad az\quad +\quad cx\\ \quad \quad \quad z\quad =\quad bx\quad +\quad ay\\ \\ then\quad show\quad that\quad :\quad \frac { { x }^{ 2 } }{ 1-{ a }^{ 2 } } =\frac { { y }^{ 2 } }{ 1-{ b }^{ 2 } } =\frac { { z }^{ 2 } }{ 1-{ c }^{ 2 } } \)
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Kindly show us your attempt at the answer and where you're getting stuck.
From equation for y and z we have
x=cy−az=bz−ay
cy+bz=cy−az then (a+bc)z=(1−c2)y−−(1)
cy+bz=bz−ay then (a+bc)y=(1−b2)z−−(2)
(1)÷(2)=yz=(1−b2)z(1−c2)y
Thus 1−b2y2=1−c2z2 then do the same for x and a you will get what are you seeking for.
Log in to reply
nice solution